Effects of nitrogen addition and Bothriochloa ischaemum and Lespedeza davurica mixture on plant chlorophyll fluorescence and community production in semi-arid grassland - Wang, Fugang; Shi, Lei; Zhang, Ruiyi; Xu, Weizhou; Bo, Yaojun (Frontiers in Plant Science, 2024)
Grass-legume mixture can effectively improve productivity and stimulate overyielding in artificial grasslands, but may be N-limited in semi-arid regions. This study investigated the effects of N addition on chlorophyll fluorescence and production in the grasslegume mixtures community. An N addition experiment was conducted in the Bothriochloa ischaemum and Lespedeza davurica mixture community, with seven mixture ratios (B0L10, B2L8, B4L6, B5L5, B6L4, B8L2, and B10L0) according to the sowing abundance of B.ischaemum and L.davurica and four N addition levels, N0, N25, N50, and N75 (0,25,50,75kgNhm-2a-1 ), respectively. We analyzed the response of chlorophyll fluorescence parameters of the two species, the rapid light-response curves of chlorophyll fluorescence, as well as aboveground biomass (AGB) and overyielding. Our results showed that the two species showed different photosynthetic strategies, with L.davurica having significantly higher initial fluorescence (Fo), effective photochemical quantum yield of PSII (ΦPSII), and coefficient of photochemical fluorescence quenching (qP) than B. ischaemum, consistenting with results of rapid light-response curves. N addition and mixture ratio both had significant effects on chlorophyll fluorescence and AGB (p<0.001). The ΦPSII and qP of L.davurica were significantly lowest in B5L5 and B6L4 under N addition, and the effect of N varied with mixture ratio. The photosynthetic efficiency of B. ischaemum was higher in mixture than in monoculture (B10L0), and ΦPSII was significantly higher in N50 than in N25 and N50 at mixture communities except at B5L5. The community AGB was significantly higher in mixture communities than in two monocultures and highest at B6L4. In the same mixture ratio, the AGB was highest under the N50. The overyielding effects were significantly highest under the N75 and B6L4 treatments, mainly attributed to L.davurica. The partial least squares path models demonstrated that adding N increased soil nutrient content, and complementary utilization by B.ischaemum and L.davurica increased the photosynthetic efficiency. However, as the different photosynthetic strategies of these two species, the effect on AGB was offset, and the mixture ratio's effects were larger than N. Our results proposed the B6L4 and N50 treatments were the optimal combination, with the highest AGB and overyielding, moderate grass-legume ratio, optimal community structure, and forage values.